Use of Vermicompost from Sugar Beet Pulp in Cultivation of Peas (Pisum sativum L.) - Grzegorz Pączka; Anna Mazur-Pączka; Mariola Garczyńska; Edmund Hajduk; Joanna Kostecka; Izabela Bartkowska; Kevin R. Butt (Agriculture, 2021)
A properly conducted vermicomposting process is an environmentally friendly technology used to transform selected organic waste into vermicompost. This organic fertilizer is increasingly used in agriculture and horticulture as an alternative to mineral fertilizers. Research has investigated the use of vermicompost made from the waste mass of sugar beet pulp as a soil additive in the cultivation of peas (Pisum sativum L.). Experimentally, five treatments consisted of: a heavy clay soil as control (SL); the same soil with 10, 25, and 50% substitution of vermicompost, (V10, V25, and V50, respectively); and a standard peat-based horticulture substrate (GS) for comparison. Analyzed pea characteristics and the content of macro and microelements in their biomass were most favorably influenced by 25 and 50% vermicompost addition, and the values obtained were similar to those in the GS treatment. The lowest values of analyzed traits for P. sativum were found in the SL group. Thus, appropriate addition of vermicompost in the construction of plant growing substrates can reduce the use of inorganic fertilizers and be an alternative to peat in the medium, contributing to reduced use of this valuable environmental resource.